How Landscapes and History Shape Copper in Vineyard Soils: Example of Fruška Gora Region, Serbia - Irina Andreeva; Valeria Gabechaya; Dmitriy Morev; Miljan Samardžić; Zoran Galić; Alexis Yaroslavtsev (Land)
Vineyards are distinctive agroecosystems heavily influenced by local natural factors and traditional management practices, with significant implications for the quality and quantity of grape production. This study investigated the ecological impact of copper-containing fungicides on the accumulation and distribution of copper, manganese, chromium, and cobalt in the upper soil horizons of vineyards of varying ages in the Fruška Gora region, Serbia. The results indicated a marked difference in total copper content across vineyards, with the oldest vineyard exhibiting levels 6.9 times above the regulatory limit. Factor analysis delineated a strong correlation between copper accumulation and vineyard age while also highlighting the influence of landscape morphology on the spatial distribution of heavy metals. The findings suggest that copper accumulation is primarily related to agricultural practices, particularly the duration of fungicide application, while the distribution of other heavy metals is more closely associated with topographic features. The novelty of our research lies in the fact that we have shown that the assessment of copper accumulation in soil in vineyard ecosystems should take into account not only viticultural practices but also the history of land use and the landscape characteristics of the area.